DIGITAL PLATFORMS AND ECOSYSTEMS: REDEFINING BUSINESS MODELS IN THE AGE OF CONNECTIVITY (AUN INTERNATIONAL CONFERENCE, 2025)
In today's hyper-connected world, digital platforms and ecosystems have emerged as powerful drivers of business innovation and transformation. This paper explores the profound impact of digital platforms and ecosystems on traditional business models, highlighting their role in reshaping industries, fostering innovation, and creating new avenues for value creation. In this research, we look into the dynamics of these ecosystems, emphasizing the interplay between technology, data, and network effects that drive their growth. Furthermore, the challenges and opportunities presented by the age of connectivity, emphasizing the need for strategic adaptation in the face of evolving consumer behaviors and emerging technologies. By examining real-world case studies and offering insights from various industries, this paper aims to provide a comprehensive understanding of the evolving landscape of business models in the digital era and offers valuable takeaways for practitioners and scholars seeking to thrive in this dynamic environment.